Akkermansia muciniphila and herbal medicine in immune-related diseases: current evidence and future perspectives - Ding, Xue; Meng, Peng-Fei; Ma, Xiu-Xia; Yue, Jing-Yu; Li, Liang-Ping; Xu, Li-Ran (Frontiers in Microbiomes, 2024)
Akkermansia muciniphila is considered the "paradigm for next-generation beneficial microorganisms" and has been reported to help alleviat immune-related diseases. Evidence shows that herbal medicine can treat disease by regulating the abundance of A. muciniphila. Recent studies have revealed a link between A. muciniphila and immune-related diseases. Here, we systematically reviewed the association between A. muciniphila, herbal medicine , and immune-related diseases (including inflammatory bowel disease, human immunodeficiency virus, cancer immunotherapy, and immune-related liver injury). We also summarize the potential mechanisms of action of A. muciniphila and offer perspectives for future studies.